Lemongrass oil-based aromatherapy balm innovation for muscle pain reduction and body relaxation - Kadang, Yuniharce; Patandung, Gerfan (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Muscle pain is a common condition that affects individuals of various ages due to physical strain, fatigue, or improper posture. Conventional balms often rely on synthetic chemical agents that may cause irritation or excessive heat sensation. Therefore, developing a natural-based topical formulation with dual functions pain reduction and body relaxation has gained growing attention. Lemongrass oil (Cymbopogon citratus) contains active compounds such as citral, geraniol, and limonene, known for their analgesic, anti-inflammatory, and aromatherapeutic properties. This study aimed to innovate an aromatherapy balm using lemongrass essential oil to provide both pain relief and a relaxing effect on the body. Methods: This experimental laboratory study employed a post-test-only design. The balm was formulated with varying concentrations of lemongrass oil (5%, 10%, and 15%), beeswax, vaseline, coconut oil, and menthol. The formulations underwent organoleptic evaluation, skin irritation testing, and effectiveness assessment on mild muscle pain using the Visual Analog Scale (VAS). Ten respondents with muscle discomfort applied the balm twice daily for three days. Data were analyzed descriptively to compare the physical stability, acceptability, and pain reduction effectiveness of each concentration. Results: All formulations demonstrated good physical stability, showing no color or odor alteration after 14 days of storage. Organoleptic evaluation revealed that the 10% lemongrass oil concentration was the most preferred, exhibiting a pleasant aroma and smooth texture. Effectiveness testing indicated that the 10% balm reduced pain intensity by an average of 40%, outperforming the 5% (25%) and 15% (38%) formulations. No cases of skin irritation were reported. Respondents also reported a sense of calmness and relaxation attributed to the aromatherapeutic properties of lemongrass. Conclusion: The aromatherapy balm containing 10% lemongrass oil provides optimal pain relief and relaxation effects without adverse skin reactions. This innovation offers a promising alternative to conventional synthetic balms, aligning with the growing demand for safe, natural, and eco-friendly complementary therapies.